Factors affecting the quality and reproducibility of MALDI-TOF MS identification for human Capnocytophaga species - Algahawi, Ahmed (Netherlands, 2025)
Reproducibility and quality of MALDI-TOF MS spectra are critical in the identification process, however, information on the factors affecting the identification scores are scarce. Here, we studied the influence of various factors during the identification process of human oral Capnocytophaga species. The influence of two incubation times, plate-spotting reproducibility of two examiners, extraction technique, storage period of plates, and different laser repetition rates on the quality of MALDI-TOF MS identification of 34 human Capnocytophaga strains (including C. gingivalis, C. granulosa, C. haemolytica, C. leadbetteri, C. ochracea, C. sputigena, and Capnocytophaga genospecies AHN8471) was examined. The identification rate did not show a significant difference (P = 0.05) between the two incubation times, except that C. haemolytica needed a longer incubation time to be recognized at the genus level. The reproducibility of spotting between two examiners was ensured by following the manufacturer's instructions. At the species level, formic acid extraction improved the identification of species with limited representation in the database, such as C. haemolytica and C. granulosa. The storage of plates for one week decreased the identification scores. No significant difference (P = 0.39) was observed between the 60 Hz and 120 Hz laser repetition rates for identifying Capnocytophaga species to the genus or species level. In conclusion, the MALDI TOF MS offers a reliable Capnocytophaga identification after following the universal protocol, while the formic acid extraction is restricted to species with a limited number of strains in the database.